Equipping the churches in the healing ministry curriculum Consultation for Asian Churches in health, healing and wholeness - Curriculum Consultation for Asian Churches in Health, Healing, and Wholeness (1992: Manila, Philippines); Christian Conference of Asia. Development and Service (Osaka Christian Conference of Asia, Development and Service, 1992)
papers presented at a conference held in Manila, Philippines, during Mar. 1992
Keywords: Spiritual healing -- Asia -- Congresses; Healing -- Asia -- Religious aspects -- Congresses; Health -- Religious aspects -- Christianity